Occurrence of antibiotics in the selected hospitals and municipal wastewater system of Nepal - Bhatta, Rita; Bhattrai, Shreeya; Shyaula, Sajan Lal; Joshi, Rajendra (Nepal Journal of Environmental Science, 2025)
Hospital wastewater is contaminated with antibiotics excreted by inward patients and laboratory leftovers. This study aims to evaluate the occurrence of commonly prescribed antibiotics in two hospitals (Hospital 1 and Hospital 2) wastewater stream and Guheshwori municipal wastewater treatment plant by employing high performance liquid chromatography (HPLC). Identification of the most commonly prescribed antibiotics was done through questionnaire survey. For analysis, composite sampling was done following 3 days/24 hours mixing. HPLC (Agilent 1260 infinity II) system was used with DAD detector and binary pump. By matching the retention time with standards, samples (antibiotics) were identified, and the concentration of each identified antibiotic was determined by peak area calculation. Results indicate that amoxicillin, cefixime, ampicillin, ciprofloxacin, azithromycin, ceftriaxone, metronidazole and cloxacillin are the most commonly used antibiotics in Hospital 1 and Hospital 2. Study of physico-chemical parameters of the wastewater reveals the slightly alkaline pH, high electrical conductivity, high total dissolved solid and also high BOD & COD values. Interestingly, ceftriaxone and ciprofloxacin are detected in the inlet and outlet samples of hospital wastewater, and their concentration was reduced in outlet samples. From this study, antibiotics, albeit in low concentration, are detected in hospital wastewater and thus antibiotic specific water treatment system is recommended.